Techniques for fabricating hollow obturator: Two case reports - Janakirama Reddy Sridevi; Natarajan Kalavathy; Narasimha Jayanthi; Narasimhaiah Manjula (Wolters Kluwer Medknow Publications, 2014)
The most commonly seen intraoral defect is the one affecting the maxilla, through an opening into the nasopharynx. These defects can either be congenital or acquired. These are usually large openings in the palate and/or the surrounding structures. Obturators are used to close or seal these defects to restore proper mastication, speech, deglutition, and esthetics. This article presents case reports describing two different techniques for fabricating hollow bulb oburator.